PENENTUAN MODEL TERBAIK REGRESI RIDGE DAN TERAPANNYA - Sri Utami Zuliana (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2018)
Ridge regression is one of penalized regression methods. Penalized regression methods are usually used for solving the problem of multicollinearity. The best model in ridge regression has been chosen by some previous techniques. In the techniques there is bias-variance trade-off. In this paper, Schall algorithm will be applied for choosing the best model. Schall algorithm is faster because it only needs a few iteratives to be convergence.